2016
DOI: 10.1186/s13063-016-1270-z
|View full text |Cite
|
Sign up to set email alerts
|

Atraumatic Restorative Treatment compared to the Hall Technique for occluso-proximal cavities in primary molars: study protocol for a randomized controlled trial

Abstract: BackgroundIn many parts of the world, school-age children have high dental treatment needs; however, there is often low, or no, dental care provision. Although Atraumatic Restorative Treatment (ART) was developed to address this, its survival rate in occluso-proximal lesions is low. An alternative, the Hall Technique (HT) has shown better relative outcomes for occluso-proximal lesions, but has not been directly compared to ART or tested in field settings. This trial will compare ART and the HT for the most cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
13

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 46 publications
1
37
0
13
Order By: Relevance
“…This reinforces previous qualitative study which showed that child oral health can impact their family's quality of life, contributing to stress, financial challenges, and at times affecting their physical health . It has been shown that cavitated lesions can make parents upset and feeling guilty about the condition of their children . Studies have showed that poor parental perception on OHRQoL and toothache in children was associated with parental guilt .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This reinforces previous qualitative study which showed that child oral health can impact their family's quality of life, contributing to stress, financial challenges, and at times affecting their physical health . It has been shown that cavitated lesions can make parents upset and feeling guilty about the condition of their children . Studies have showed that poor parental perception on OHRQoL and toothache in children was associated with parental guilt .…”
Section: Discussionmentioning
confidence: 99%
“…14 It has been shown that cavitated lesions can make parents upset and feeling guilty about the condition of their children. 18 Studies have showed that poor parental perception on OHRQoL and toothache in children was associated with parental guilt. 2,19,20 According to Guedes et al, 21 parents usually feel responsible for the well-being of their children.…”
Section: Discussionmentioning
confidence: 99%
“…22 İnvaziv olmayan dizaynı, hasta tarafından kabul edilebilmekte ve uzun ömürlü bir restorasyon oluşundan dolayı tedavi edilmemiş süt dişi oranlarında düşüş sağlayabileceği düşünülmektedir. 23,24 Yapılan bir çalışmada, hem ailelerin hem de çocukların büyük çoğunluğunun PÇK'nin Hall tekniği ile uygulanmasından memnun olduğu; görüntü, ağrı ve prosedürün kabul edilebilir bulunduğu bildirilmiştir. 25 …”
Section: Hall Tekni̇ği̇unclassified
“…Aile ve çocuk, Hall kronların estetik sonuç-larından memnuniyet duymayacak ise, Bu konuyla alakalı yapılan bir çalışmada, ailelerin PÇK'lerin estetiğinden memnun olmadığı ve bunun Hall tekniği açısından bir limitasyona neden olabileceği belirtilmiştir. 23 Otistik çocuklarda Hall tekniği kullanımının uygun olmayabileceği belirtilmiştir. 33 Eğer hasta bakteriyel endokardit açısından risk altında ise bütün çürük dokusunun uzaklaştırıl-dığı konvansiyonel yöntemler tercih edilmelidir (Evans D, Innes N. The Hall Technique.…”
Section: Konvansi̇yonel Yöntemlerde Di̇ş çüRüğü Tamamen Temi̇zleni̇rken Hunclassified
See 1 more Smart Citation